Applying the #Z# transform
#Y(z)-z^-1Y(z)+0.9z^-2Y(z)=X(z)# or
#Y(z)(1-z^-1+0.9 z^-2) = X(z)#
and then
#Y(z) = 1/(1-z^-1+0.9 z^-2) X(z)#
now
#X(z) = 1# for unit impulse and
#X(z) = 1/(1-z^-1)# for an step function
and the response is obtained by anti-transforming
#Y_1(z) = (1/(1-z^-1+0.9 z^-2)) (1) = z^2/((z-0.5+0.806666i)(z-0.5-0.806226i))#
#Y_2(z) = (1/(1-z^-1+0.9 z^-2)) (1/(1-z^-1)) = z^3/((z-0.5+0.806666i)(z-0.5-0.806226i)(z-1))#
with
#y_n = (0.5 + 0.310087 i) e^((-0.0526803 - 1.01568 i) n) + (0.5 -
0.310087 i) e^((-0.0526803 + 1.01568 i) n)#
as the impulsive response and
#y_n=1.11111 - (0.0555556 -
0.58572 i) e^((-0.0526803 - 1.01568 i) n) - (0.0555556 +
0.58572 i) e^((-0.0526803 + 1.01568 i) n)#
as the step function response.